Penelitian Evaluasi Di SMAN 1 Kota Probolinggo dalam Persiapan Turnamen Basket Walikota Cup - Roudhotul Janah; Agung Yudha Catur Rizal; Rosi Rosalina (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aimed to evaluate the preparations for the 2023 Mayor's Cup Invitation Basketball Championship. This study used a quantitative descriptive methodology. The subject of this study was the Principal of SMAN 1 Proboliggo City, which consisted of 1 person. Two extracurricular coaches, four people in charge of facilities and infrastructure, and 22 athletes. Information collection methods through questionnaires and written notes. The Pearson product-moment correlation test performed in SPSS at a significance level of 5% was used to verify the accuracy of the data. Data analysis involves using numerical descriptions with percentages to assess trend significance. Here are some ways to present the findings of the data analysis: 82% (18) of athletes rated